Pengaruh Firm Size dan Capital Structure terhadap Earning Quality: Studi pada Perusahaan Farmasi yang Terdaftar di BEI (2019–2023) - Maulana, Rizky Akbar; Mulyandini, Vita Citra (Ekonomis: Journal of Economics and Business, 2026)
This study aims to examine the effect of firm size and capital structure on earnings quality in pharmaceutical manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2023 period. This study uses a quantitative approach with a causal-comparative design. The sample was selected using a purposive sampling technique, and 10 companies with data spanning five years were obtained. Data were analyzed using multiple linear regression. The results show that simultaneously, firm size and capital structure variables do not significantly influence earnings quality in pharmaceutical manufacturing companies listed on the Indonesia Stock Exchange during the 2019–2023 period. This finding suggests that in the context of the pharmaceutical subsector, firm size and capital structure are not strong enough to explain variations in earnings quality, so exploration of other more relevant variables is needed.